Sensorless Control of Permanent Magnet Synchronous Motor Using Voltage Signal Injection - Brandstetter, P.; Krecek, T. (Elektronika ir Elektrotechnika, 2013)
A successful application of vector control is subject to knowing the position of the rotor and, in synchronous machines, the knowledge of the initial position for a problem-free startup. The ability to read rotor position and perform the vector control algorithm without a position sensor is typically referred to as sensorless vector control. Traditional feedback from the rotor position sensor, or the sensor of mechanical angular velocity of the motor, is typically replaced with a computational block or an algorithm that uses the measured voltage and current to indicate the actual position of the motor. The article presents a sensorless control of the permanent magnet synchronous motor using an injection of high frequency voltage for rotor position estimation. DOI: http://dx.doi.org/10.5755/j01.eee.19.6.1583